Back Pain in Poland and Germany: A Survey of Prevalence and Association with Demographic Characters. (1st July 2014) - Henn, Lea; Schier, Katarzyna; Brian, Tamara; Hardt, Jochen
Abstract : Background. Back pain is the most common form of pain and leads to high costs in all medical care systems. Objective. The present study examines the prevalence of back pain and its associations with some basic demographics. Methods. Two samples from Poland and Germany (about n = 500 each) were examined via Internet regarding back pain, gender, age, and body mass index (BMI). Results. Back pain is more common in women than in men (risk ratio about 1.7), and a high BMI constitutes an additional risk factor. Age was not related to back pain prevalence. Conclusion. Congruent results in two countries based on the same measure of back pain lead to the assumption that much of the variety found in estimates of back pain are due to inconsistent assessment. For future research, a definition of common criteria on how to assess back pain would be an asset.